2018
DOI: 10.1093/rheumatology/key282
|View full text |Cite
|
Sign up to set email alerts
|

Association of antibodies against myelin and neuronal antigens with neuroinflammation in systemic lupus erythematosus

Abstract: Anti-NS antibodies, most prevalently anti-MOG antibodies, are significantly associated with NPSLE and manifest with the distinct neurological syndrome associated with the antibody in a subgroup. Follow-up studies in large, independent cohorts will reveal whether these anti-NS antibodies could serve as a diagnostic and prognostic biomarker for NPSLE and enable tailored treatment decisions in this challenging and diverse patient cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…Overall, AQP4-IgG antibodies have been detected in 0.6-3% and 10% of SLE and pSS cohorts, respectively. [23][24][25] Nowadays, several studies have proven the high syndrome specificity of AQP4-IgG antibodies, as these autoantibodies have not been detected in sera of patients with SLE/pSS without NMOSD features. 18,23,25,26 Pittock et al reported that only SLE/pSS patients with NMOSD clinical syndromes were AQP4-IgG seropositive in an American and a French cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, AQP4-IgG antibodies have been detected in 0.6-3% and 10% of SLE and pSS cohorts, respectively. [23][24][25] Nowadays, several studies have proven the high syndrome specificity of AQP4-IgG antibodies, as these autoantibodies have not been detected in sera of patients with SLE/pSS without NMOSD features. 18,23,25,26 Pittock et al reported that only SLE/pSS patients with NMOSD clinical syndromes were AQP4-IgG seropositive in an American and a French cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The Swiss SLE Cohort Study Group demonstrated that antibodies against components of nervous system were found in 13% (23/174) of total SLE populations, and anti-myelin oligodendrocyte glycoprotein antibody was significantly associated with NP-SLE. [ 28 ] Besides, some classic antibodies, such as anti-phospholipid, anti-ribosomal P, and anti-aquaporin 4 antibodies are implicated in NP-SLE. Nevertheless, no gold standard has been established for the diagnosis of NP-SLE so far.…”
Section: Advances On Clinical Manifestations In Slementioning
confidence: 99%
“…In AQP4 autoantibody–positive NMOSD, autoantibodies that relate to SLE such as ANA and dsDNA are frequently encountered (17). In SLE, AQP4 autoantibodies and concurrent NMOSD manifestations are also reported (36, 37, 41, 42). Importantly, AQP4 autoantibodies have been found to be present in the peripheral blood of SLE patients or in a single healthy individual, both without clinical evidence of NMOSD or CNS involvement (37, 43, 44); in the case of the healthy individual, NMOSD became clinically manifested 10 y later.…”
Section: Discussionmentioning
confidence: 97%
“…In SLE, AQP4 autoantibodies and concurrent NMOSD manifestations are also reported (36, 37, 41, 42). Importantly, AQP4 autoantibodies have been found to be present in the peripheral blood of SLE patients or in a single healthy individual, both without clinical evidence of NMOSD or CNS involvement (37, 43, 44); in the case of the healthy individual, NMOSD became clinically manifested 10 y later. For disease to manifest, it may be that a second event induces blood-brain barrier permeability to allow serum AQP4 IgG and/or AQP4 autoantibody–expressing B cells to enter the CNS (45, 46).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation